Ergonomic Interventions At Badger Mining Corporation (30a13109-bb6a-4698-a288-c4dfde51a853) - J. Torma-Krajewski; M. Lehman (Society for Mining, Metallurgy & Exploration, 2007)
In 2005, NIOSH and Badger Mining Corporation entered a partnership to implement ergonomic interventions, including a systematic process, to address exposures to risk factors that may result in musculoskeletal disorders or other types of injuries/illnesses. As a result of this partnership, an ergonomics process was integrated with the existing safety and health program to promote an on-going application of ergonomic principles, and over 40 task-specific interventions were implemented during the first year of the process. This paper presents details of the process integration, and several examples of task-specific interventions that reduced exposures to risk factors.